Down and dirty the essential training guide for obstacle races and mud runs - Davis, Matt B. (Fair Winds Press, 2014)
Obstacle course races and mud runs such as Tough Mudder, Spartan Race, Warrior Dash, Rugged Maniac, and Muddy Buddy are all waiting for you to get Down and Dirty. Author Matt B. Davis offers an overview of the most popular races before tackling the most important concerns for any racer: preparation and training. Each obstacle-focused chapter will feature a leading obstacle race athlete who will offer expert advice on how to get prepared for your next race--whether it's your first or you're a recent devotee who wants to try them all. Because each race is different, this book will supply training advice for a variety of obstacles and races. -- Provided by publisher.